The Impact of the Seaweed Cultivation Infrastructure Provision Program on Farmers' Productivity and Income in Central Buton Regency - Rahman; Gunawan; Upacha, Syahdan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzes the impact of the seaweed cultivation infrastructure provision program on the productivity and income of farmers in Central Buton Regency. The program successfully introduces modern technologies and training that improve production efficiency, allowing farmers to harvest faster and produce high-quality products. The results of interviews with farmers showed that more than 60% experienced an increase in income after participating in the training, and their technical skills in seaweed cultivation improved significantly. Despite challenges in aid distribution and price fluctuations, effective communication between the government and farmers is essential to ensure equitable access to infrastructure. This research emphasizes the need for sustainability of training programs, especially in marketing, to increase the competitiveness of seaweed products in local and international markets. These findings provide recommendations for improving the distribution system and increasing technical support to farmers to encourage local economic growth and the welfare of coastal communities.